2018
DOI: 10.1038/s41378-018-0039-9
|View full text |Cite
|
Sign up to set email alerts
|

Glassy carbon microneedles—new transdermal drug delivery device derived from a scalable C-MEMS process

Abstract: Because carbon is the basic element of all life forms and has been successfully applied as a material for medical applications, it is desirable to investigate carbon for drug delivery applications, as well. In this work, we report the fabrication of a hollow carbon microneedle array with flow channels using a conventional carbon-microelectromechanical system (C-MEMS) process. This process utilizes the scalable and irreversible step of pyrolysis, where prepatterned SU-8 microneedles (precursor) are converted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…Figure 11 shows the SEM image of one the fabricated SU-8 microneedle arrays using SU-8 itself as microneedle structural material. Mishra et al’s work started with the fabrication of high-aspect-ratio SU-8 hollow structures [ 65 ]. The hollow SU-8 structures were then subsequently pyrolyzed in an inert atmosphere at 900 °C to convert the SU-8 structures into glassy carbon structures.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 11 shows the SEM image of one the fabricated SU-8 microneedle arrays using SU-8 itself as microneedle structural material. Mishra et al’s work started with the fabrication of high-aspect-ratio SU-8 hollow structures [ 65 ]. The hollow SU-8 structures were then subsequently pyrolyzed in an inert atmosphere at 900 °C to convert the SU-8 structures into glassy carbon structures.…”
Section: Applicationsmentioning
confidence: 99%
“…( f , g ) Magnified images of the CMNs and the underlying flow channel. Reprinted from Mishra et al [ 65 ] with permission from Springer Nature.…”
Section: Figurementioning
confidence: 99%
“…This study mainly analyzed MNs flexibility and concluded that this feature could be tuned depending on the required application. Another relevant studies, reported the design, fabrication and characterization of a hollow glassy carbon MN array (Pramanick et al, 2016) with flow channel integration (Mishra et al, 2018). The strategy was based on the direct laser writing patterning of photoresist as precursor and conversion of these structures into glassy carbon by pyrolysis retaining their tubular MN shape.…”
Section: Needle-based Transdermal Drug Delivery Devicesmentioning
confidence: 99%
“…(C) a: Etched microfluidic conduit in silicon through which the drug flows from the drug reservoir to the glassy carbon microneedles; b: SU-8 microneedles fabricated on a microfluidic conduit backside of the image shown in a; c: glassy carbon microneedles array formed after pyrolysis; d: magnified view of a glassy carbon microneedles; e: optimized glassy carbon microneedles aligned on etched microfluidic ports on a silicon wafer. Adapted fromMishra et al (2018) with permission from Springer Nature (http://creativecommons.org/licenses/by/4.0/).…”
mentioning
confidence: 99%
“…The biocompatibility of scaffolds is first influenced by the types of materials used. Recently, various materials were investigated, including metal, ceramic, natural, and synthetic [ 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%